Advancements in LAM-based diagnostic kit for tuberculosis detection: enhancing TB diagnosis in HIV-negative individuals - Gao, Man; Wu, Qianhong; Wang, Xinhong; Sun, Xiuli; Li, Meng; Bai, Guanghong (Frontiers in Microbiology, 2024)
Objective: The purpose of this study was to investigate the diagnostic value of urine lipoarabinomannan (LAM) detection based on chemiluminescence assay for pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB) in HIV-negative individuals.Methods: A total of 215 patients and 37 healthy individuals were included according to inclusion and exclusion criteria, including 173 cases of PTB and 42 cases of EPTB. Sputum smears, sputum culture, TB-RNA, GeneXpert, and urine LAM results were obtained from all patients before treatment. Using the composite reference standard as the reference, the diagnostic performance of these methods for PTB and EPTB was evaluated, and the diagnostic performance and cost-effectiveness of different combinations were analyzed.In PTB, LAM exhibited the highest sensitivity (55.49%), followed by GeneXpert (44.51%).In EPTB, LAM also had the highest sensitivity (40.48%), followed by GeneXpert (33.33%). When combined with one method, LAM combined with GeneXpert showed the highest sensitivity for both PTB (68.79%) and EPTB (61.9%). When combined with two methods, culture, GeneXpert, and LAM showed the highest sensitivity for both PTB (73.99%) and EPTB (69.05%). In terms of costeffectiveness analysis, the price of LAM was significantly lower than that of GeneXpert (＄129.82 vs ＄275.79 in PTB and 275.79 vs 502.33 in EPTB). Among all combinations, the combination of LAM and sputum smear had the lowest cost, with prices of ＄124.94 for PTB and ＄263.72 for EPTB.Urine LAM detection based on chemiluminescence assay can be used as an adjunct diagnostic tool for PTB and EPTB in HIV-negative individuals. This facilitates expanding the current application of urine LAM from solely HIV-positive populations to the general population. LAM detection can overcome the limitations of obtaining clinical samples, and its ease of sample acquisition will be beneficial for its broader application in a larger scope. For economically better-off areas, we recommend using a combination of LAM+GeneXpert+culture for higher sensitivity; for economically disadvantaged areas, LAM+smear microscopy combination can provide a quick and accurate diagnosis of tuberculosis at a lower cost.